Novel tactical insights from Men`s 2022 FIFA World Cup: Which performance indicators explain the teams` goal difference? - Praça, G. M.; Brandão, L. H. A.; Abreu, C. O.; de A. Oliveira, P. H.; de Andrade, A. G. P. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
This study examined positional and event-based tactical variables during the Men`s 2022 FIFA World Cup to detect differences between winning and losing teams and to verify which variables would better predict the goal difference between the teams. All 64 matches played during the competition were initially considered. Due to the purpose of the current article, draw matches were excluded from the sample. The data were compared between the match statuses using a MANOVA. A stepwise multiple linear regression was used to detect which variables predict the outcome of the matches. Results indicated differences between winning and losing in Line Breaks per Pass (p = 0.011), Defensive Line Break per Pass (p = 0.004), Final Third Phase Height (p = 0.023), and Width (p < 0.001). The best predictors of the goal difference were the Final Third Phase Width (standardized beta = -0.389), the Completed Line Breaks (standardized beta = 0.716), and the movements to receive in the progression phase in between (standardized beta = -0.491). It is concluded that positioning the team closer to the central corridor in the last third of the pitch and successfully breaking the defensive lines increases winning probability during the competition.